Effectiveness of Using a Constant Coefficient in Combining Forecasts to Improve Forecasting Accuracy - A. A. Surkov (Учёт. Анализ. Аудит, 2024)
The article discusses the methodology for using a constant coefficient when combining forecasts. Today, there are many options for constructing weighting coefficients, and some of them include a constant coefficient in the combination due to the assumption that it improves forecasting accuracy. Unfortunately, there is no clear and unambiguous answer to the question of how true this hypothesis is — it has both positive and negative sides. The purpose of the study is to determine the advantages and disadvantages of using a constant coefficient when combining forecasts based on available practical and theoretical data, as well as to form a unified approach to this issue. In the course of the work, scientific methods for combining forecasts were applied (proposed by K. Granger and R. Ramanathan), one of which involves the presence and calculation of the constant coefficient. The practical results obtained by the author of the article have generally confirmed the value of including a constant coefficient in the combined forecast, on the basis of which it was concluded that the use of the latter is possible if there is confidence that it can improve the accuracy of forecasting. The study also identified the need to find such an approach to constructing weighting coefficients that would take into account the possibility of changing the constant coefficient for combining forecasts, thereby expanding the possibilities of its application.